2024
DOI: 10.2340/actadv.v104.19454
|View full text |Cite
|
Sign up to set email alerts
|

Real-world Experience of Abrocitinib Treatment in Patients with Atopic Dermatitis and Hand Eczema: Up to 28-week Results from the BioDay Registry

Esmé Kamphuis,
Celeste M. Boesjes,
Laura Loman
et al.

Abstract: Limited daily practice data on the effect of abrocitinib in patients with atopic dermatitis are available. The aim of this multicentre prospective study is to evaluate the effectiveness and safety of abrocitinib in patients with atopic dermatitis treated in daily practice. In a subgroup, the effectiveness of abrocitinib on hand eczema was evaluated. A total of 103 patients from the BioDay registry were included in the study: week 4 (n = 95), week 16 (n = 61) and week 28 (n = 39). At week 28, the Eczema Area an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 34 publications
(60 reference statements)
0
4
0
Order By: Relevance
“…We found nine studies on the risk of neoplasms with selective JAK 1 (JAK-1) inhibitors: three focusing on abrocitinib [ 77 , 99 , 100 ] and six on upadacitinib [ 55 , 101 105 ]. In the three studies with abrocitinib, including 787 patients with AD, no cases of cancer were reported [ 77 , 99 , 100 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We found nine studies on the risk of neoplasms with selective JAK 1 (JAK-1) inhibitors: three focusing on abrocitinib [ 77 , 99 , 100 ] and six on upadacitinib [ 55 , 101 105 ]. In the three studies with abrocitinib, including 787 patients with AD, no cases of cancer were reported [ 77 , 99 , 100 ].…”
Section: Resultsmentioning
confidence: 99%
“…We found nine studies on the risk of neoplasms with selective JAK 1 (JAK-1) inhibitors: three focusing on abrocitinib [ 77 , 99 , 100 ] and six on upadacitinib [ 55 , 101 105 ]. In the three studies with abrocitinib, including 787 patients with AD, no cases of cancer were reported [ 77 , 99 , 100 ]. Regarding upadacitinib, a recent SR including 25 RCTs (> 10,000 patients) reported that most of the RCTs did not find a significant increase in the rate of malignancies with upadacitinib therapy when compared to placebo or to anti-TNFs [ 101 , 103 , 105 ].…”
Section: Resultsmentioning
confidence: 99%
“…Sitaru et al ( 10 ) reported a case of refractory hand and foot eczema was successfully treated with abrocitinib. Kamphuis et al ( 11 ) demonstrated that abrocitinib improved HE in patients with AD in which 13/17 of the patients achieved clear or almost clear and 60% of the patients achieved HECSI 90 at week 16. In our study, all patients reached HECSI 90 and 9/12 of the patients achieved an IGA score of 0/1 at week 16.…”
Section: Discussionmentioning
confidence: 99%
“…It blocks IL-4, IL-13, IL-31, and IFN-γ pathways, which are involved in the pathogenesis of HE ( 9 ). However, the efficacy of abrocitinib on difficult-to-treat HE in real-world is limited ( 10 , 11 ). Here, we reported the effectiveness and safety of abrocitinib on difficult-to-treat HE patients in daily practice.…”
mentioning
confidence: 99%